2014
DOI: 10.1016/j.whi.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Employment During Pregnancy and Obstetric Intervention Without Medical Reason: Labor Induction and Cesarean Delivery

Abstract: Background Rising rates of labor induction and cesarean delivery, especially when used without a medical reason, have generated concern among clinicians, women, and policymakers. Whether employment status affects pregnant women's childbirth-related care is not known. We estimated the relationship between prenatal employment and obstetric procedures, distinguishing whether women reported that the induction or cesarean was performed for medical reasons. Methods Using data from a nationally-representative sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Being employed was associated with a mother delivering through CS among women in Nairobi, Kenya. Studies in the United States and Brazil also found that employed women who were employed prenatally were more likely to deliver through CS compared to unemployed women [ 11 , 12 ]. We also found that mothers who underwent CS were at lower odds of having babies with normal birth weights because many of the low birth weight babies are premature and like babies with Cephalo pelvic disproportion are delivered through CS [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being employed was associated with a mother delivering through CS among women in Nairobi, Kenya. Studies in the United States and Brazil also found that employed women who were employed prenatally were more likely to deliver through CS compared to unemployed women [ 11 , 12 ]. We also found that mothers who underwent CS were at lower odds of having babies with normal birth weights because many of the low birth weight babies are premature and like babies with Cephalo pelvic disproportion are delivered through CS [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women were coded as having had a labor induction if they reported that a health care practioner had used a medical method to try to cause their labor to begin. We classified inductions as having occurred for a definitive medical reason or not for a definitive medical reason based on women's reported reasons for the induction, consistent with previously published studies (see Appendix S1 for full categorization) . Gestational lengths less than 37 completed weeks were categorized as preterm.…”
Section: Methodsmentioning
confidence: 99%